The Use of Flashcards to Promote Speaking Fluency in Primary School - ali imron sayhroni, ali imron s; Suryati, Nunung; Suharyadi; Sari Karmina (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2026)
This research is a qualitative case study exploring the use of flashcards to support English speaking practice in an Islamic boarding school with limited access to technology. Ten senior students from the IEC (Istiqlal English Club) participated in the study. Data were collected through classroom observations and semi-structured interviews, then analyzed thematically. The results revealed three main themes: (1) flashcards help students build sentence structures and improve grammar usage, (2) flashcards increase fluency, confidence, and willingness to speak, and (3) flashcards create a fun, interactive, and stress-free learning environment. While providing valuable insights, this study is limited by its small sample size and the context of a single study site. This research suggests that teachers in environments with limited technology can adopt simple learning routines using flashcards to encourage active speaking practice while providing structure and motivation for students.